O clima tropical e a dengue: uma análise como subsídio para gestão ambiental municipal - PEREIRA, Marcela Gonçalves (Universidade Federal do Pará, 2018)
Since the beginning of the 19th century, based on its geographic positioning, dengue was classified as a tropical disease due to its occurrence in greater quantity on the equator, in regions that have the characteristics of the tropical climate (VALLE; PIMENTA; CUNHA, 2015 ). However, after being controlled in the past, dengue has come to be classified as reemerging - neglected disease. Man-made urban modifications, along with climatic conditions, directly interfere with the relationship between climate, health and the environment (ARAUJO, 2010). The environmental factors also play a very important role in the occurrence of dengue, the study of the climatic characteristics of the places where they occur is a valuable source for epidemiological research (STOCCO et al., 2010). From 2007 to 2015, it was possible to observe the meteorological changes that have been occurring in the city of Belém do Pará, due to impacts caused by natural or anthropogenic sources and mainly, their impacts on the health of the population. From this, the main objective of this work was the mapping of the correlation of the temporal distribution of dengue with the meteorological parameters in seven districts that belong to the watershed of Una in the city of Belém / PA, in order to guide the public policies more Economic, sectoral, and thus, investments in the eradication of the disease. The meteorological data were obtained through conventional rain gauges of the Institute of Meteorology (INMET), located in the coordinates: Latitude: -1.43º; Longitude: -48.43; Under an altitude of 10 meters. Information on the occurrence of dengue was obtained through the Municipal Secretary of Public Health of Belém (SESMA). There was a strong correlation between rainfall data, relative humidity and compensated temperature of the river basin air with the studied disease, but the correlation varied according to seasonality and seasonality. By demonstrating that some planning factors of municipal actions contribute to the correlations of these recurrences of epidemics in this catchment area of Belém. For it was observed, based on the theoretical framework, that outbreaks should not occur in these proportions in the regions belonging to an already urbanized basin. Which makes the qualitative and sustainable actions for Belém much more costly and costly.